2015
DOI: 10.1186/s13054-015-0922-9
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcome of mechanically ventilated patients after cardiac arrest

Abstract: IntroductionThe aim of this study was to describe and compare the changes in ventilator management and complications over time, as well as variables associated with 28-day hospital mortality in patients receiving mechanical ventilation (MV) after cardiac arrest.MethodsWe performed a secondary analysis of three prospective, observational multicenter studies conducted in 1998, 2004 and 2010 in 927 ICUs from 40 countries. We screened 18,302 patients receiving MV for more than 12 hours during a one-month-period. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 44 publications
4
45
0
1
Order By: Relevance
“…Sutherasan et al showed that high tidal volume and plateau pressure with lower positive end-expiratory pressure were associated with the occurrence of severe pulmonary complications during the ICU stay in CA patients [31], suggesting a potential role of ventilator settings on outcome. Moreover, patients receiving mechanical ventilation are more exposed to high oxygen levels or abnormal carbon dioxide concentrations, which have been shown to have a significant negative impact on brain recovery after post-anoxic injury [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Sutherasan et al showed that high tidal volume and plateau pressure with lower positive end-expiratory pressure were associated with the occurrence of severe pulmonary complications during the ICU stay in CA patients [31], suggesting a potential role of ventilator settings on outcome. Moreover, patients receiving mechanical ventilation are more exposed to high oxygen levels or abnormal carbon dioxide concentrations, which have been shown to have a significant negative impact on brain recovery after post-anoxic injury [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…found that Vt decreased overtime from 8.9 ml/kg in 1998–6.5 ml/kg in 2010 in patients receiving mechanical ventilation after cardiac arrest. Higher Vt in this post-arrest population was associated with an increased occurrence of ARDS [11]. Among patients with either cardiac arrest (n = 25) or congestive heart failure (n = 26) in a cardiac intensive care unit, higher tidal volumes were associated with an increased risk of mortality [12].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical ventilation was one of the independent predictors of poor neurological outcome. Sutherasan et al showed that high tidal volume and plateau pressure with lower positive end-expiratory pressure were associated with the occurrence of severe pulmonary complications during the ICU stay in CA patients [31], suggesting a potential role of ventilator settings on outcome. Moreover, patients receiving mechanical ventilation are more exposed to high oxygen levels or abnormal carbon dioxide concentrations, which have been shown to have a significant negative impact on brain recovery after post-anoxic injury [32,33].…”
Section: Discussionmentioning
confidence: 99%